Task-irrelevant visual distractions and mindful self-regulated learning in a low-stakes computer-based assessment - Wolff, Sarah M.; Wright, Daniel B.; Hatcher, Wilson J. (Frontiers in Education, 2024)
There is growing concern for the threat of distractions in online learning environments. It has been suggested that mindfulness may attenuate the effects of distraction. The extent to which this translates to academic performance is under investigated. We aimed to investigate the relationship between task-irrelevant visual distraction, time pressure, and mindful self-regulated learning in the context of a low-stakes computer-based assessment.The study sampled 712 registered users of Prolific.co who were pre-screened current undergraduate university students. After data quality screening, 609 were retained for analyses. A 2x2 design was used. Participants were randomly assigned to: 1) a control condition, 2) a distract condition, 3) a time pressure condition, or 4) a distract and time pressure condition. All participants completed reading comprehension questions, demographic questions, and the Mindful Self-Regulated Learning Scale. RESULTS: Presenting a visual distraction increased self-reported distraction and having a clock present increased self-reported time pressure. The distraction did not have a statistically significant effect on test performance. Mindfulness was negatively correlated with test performance, self-reported distraction, and self-reported time pressure. DISCUSSION: Continuous task-irrelevant visual distractions may not be distracting enough to influence performance in low stakes testing, but they do influence self-perceptions.